Oxford Handbook of Clinical Medicine 2017
DOI: 10.1093/med/9780199689903.003.0010
|View full text |Cite
|
Sign up to set email alerts
|

Neurology

Abstract: This chapter explores neurology, including lesion location, drugs and the nervous system, cerebral blood supply, testing peripheral nerves, dermatomes and peripheral nerves, headache, migraine, blackouts, vertigo and dizziness, hearing loss and tinnitus, acute bilateral leg weakness, abnormal involuntary movements (dyskinesia), stroke, transient ischaemic attack (TIA), subarachnoid haemorrhage (SAH), intracranial venous thrombosis (IVT), subdural haematoma, extradural (epidural) haematoma, delirium (acute conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous fMRI studies on both animals and humans suggested that increased neural compensation at the cortical level could be interhemispheric for behavioral restorations after stroke (63)(64)(65). Carey and Wilkins also detected a shift of corticomotor activations from the ipsilesional to the contralesional in chronic stroke patients (53,54). The mechanism for the cortical center shift after stroke as suggested by Christian et al (50) and Chechik et al (51) was related to the neural plastic strategies by recruiting resources from contralesional (i.e., interhemispheric) and additional intrahemispheric areas.…”
Section: Finger Flexionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous fMRI studies on both animals and humans suggested that increased neural compensation at the cortical level could be interhemispheric for behavioral restorations after stroke (63)(64)(65). Carey and Wilkins also detected a shift of corticomotor activations from the ipsilesional to the contralesional in chronic stroke patients (53,54). The mechanism for the cortical center shift after stroke as suggested by Christian et al (50) and Chechik et al (51) was related to the neural plastic strategies by recruiting resources from contralesional (i.e., interhemispheric) and additional intrahemispheric areas.…”
Section: Finger Flexionmentioning
confidence: 97%
“…At the same time, normal axons in the proximity of the injured region grow and extend to the target neurons (52). Previous studies involving fMRI have predominantly reported a shift in corticomotor activations from the ipsilesional side to the contralesional side in chronic stroke patients (53,54). However, there is a lack of evidence relating to the impact that ipsilateral/contralesional corticospinal connections have on the distal muscle control during hand movements after stroke (55)(56)(57).…”
Section: Finger Extensionmentioning
confidence: 99%
“…Sarcoidosis is a rare condition involving the formation of non-caseating granulomas, often affecting multiple sites 1 . Sarcoidosis most commonly affects adults aged 20 to 40, and has the highest prevalence in Northern Europe.…”
Section: Treatment Of Sarcoidosis With Surgerymentioning
confidence: 99%